2015
DOI: 10.1177/0886260515592619
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Emotion Regulation, Executive Functioning, and Aggressive Behaviors

Abstract: Emotion regulation deficits and executive functioning deficits have independently been shown to increase vulnerability toward engaging in aggressive behaviors. The effects of these risk factors, however, have not been evaluated in relation to one another. This study evaluated the degree to which each was associated with aggressive behaviors in a sample of 168 undergraduate students. Executive functioning (cognitive inhibition and mental flexibility) was assessed with a Stroop-like neuropsychological task. Emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 35 publications
(36 reference statements)
3
31
0
3
Order By: Relevance
“…In contrast, the moderated mediation effect was not found for verbal aggression. This result is not surprising given that previous studies have shown a weaker or even null relationship between this kind of aggression and emotional regulation abilities (García‐Sancho, Salguero & Fernández‐Berrocal, ; Holley, Ewing, Stiver & Bloch, ).…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, the moderated mediation effect was not found for verbal aggression. This result is not surprising given that previous studies have shown a weaker or even null relationship between this kind of aggression and emotional regulation abilities (García‐Sancho, Salguero & Fernández‐Berrocal, ; Holley, Ewing, Stiver & Bloch, ).…”
Section: Discussionsupporting
confidence: 57%
“…Alternatively, some uncontrolled factors distinguishing past year users from non-users may better explain the observed relationship between physical abuse frequency and substance use. For example, differences in baseline cognitive functioning, emotional dysregulation, or impulsivity can also interfere with essential neuropsychological functions and associated social information processing that may contribute to aggressive behaviors (Holley, Ewing, Stiver, & Bloch, 2015;Matusiewicz et al, 2013;Tarter et al, 2003).…”
Section: <Insert Table 3 About Here>mentioning
confidence: 99%
“…The inability to properly regulate emotions, or emotional dysregulation, has been shown to underlie a range of maladaptive outcomes including aggressive behavior problems (e.g., Stieben et al, 2007; Lewis et al, 2008; Holley et al, 2017) and academic underachievement (e.g., Hawkins et al, 1999; Gumora and Arsenio, 2002; Djambazova-Popordanoska, 2016) in children. Although the past several decades have seen a steady increase in research investigating the consequences of maladaptive ER, factors that promote the development of adaptive ER remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%